Nitrene Insertion into CC and CH Bonds of Diamide Diimine Ligands Ligated to Chromium and Iron. (6th October 2015) - Heins, Spencer P.; Morris, Wesley D.; Wolczanski, Peter T.; Lobkovsky, Emil B.; Cundari, Thomas R.
Abstract: The impact of redox non‐innocence (RNI) on chemical reactivity is a forefront theme in coordination chemistry. A diamide diimine ligand, [‐CHN(1, 2‐C6 H4 )NH(2, 6‐ i Pr2 C6 H3 )2 ] n ( n =0 to −4), (dadi) n, chelates Cr and Fe to give [(dadi)M] ([1 Cr(thf)] and [1 Fe]). Calculations show [1 Cr(thf)] (and [1 Cr]) to have a d 4 Cr configuration antiferromagnetically coupled to (dadi) 2− *, and [1 Fe] to be S =2. Treatment with RN3 provides products where RN is formally inserted into the CC bond of the diimine or into a CH bond of the diimine. Calculations on the process support a mechanism in which a transient imide (imidyl) aziridinates the diimine, which subsequently ring opens.